Empirical study on the effect of financial performance on bank stock prices in Malaysia - Raisa, Carissa Aulia (2025)
The banking sector plays a crucial role in economic stability by serving as the primary intermediary for savings and investments. This study examines the impact of financial performance on bank stock prices in Malaysia from 2010 to 2023. Key financial indicators analyzed include Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Net Profit Margin (NPM). This study adopts a quantitative approach, utilizing multiple regression analysis to determine the relationship between financial performance and stock price movements. Secondary data were collected from the annual reports and financial statements of selected banks. The findings indicate that ROA has a significant positive effect on stock prices, while NPL and DER exhibit a negative relationship. These results suggest that highly profitable banks tend to gain investor confidence, whereas high credit risk may lead to declining stock prices. The findings of this study provide important implications for investors, financial analysts, and policymakers in formulating investment strategies and banking policies. This study also contributes to a deeper understanding of the factors influencing the stock market in Malaysia’s banking sector